(untitled) (Contemporary Journal of Social Science Review, 2025)
Family size is an important aspect of women’s life, unfortunately in Pakistan fertility rates are quite high in comparison to other developing countries as well as the other South Asian countries. Different studies have suggested that women participation in decision making can be helpful in reducing the fertility rates. The objective of this study is to investigate the effect of women decision making and child mortality on family size in Pakistan. For this purpose, we apply binary logistics regression. The data of this study is obtained from Pakistan Demographic and Health Survey 2017-18. The results of this study show that couple education increases family size decreases. The likelihood of family size decreases as wealth status of household increases. The outcomes show that the effect of women and husband employment on family size is negative and significant. The result shows that urban women have less family size as compared to rural women. The odd ratios indicate that those women who participate in decision-making have less family size as compared to those women who do not participate in decision-making. The likelihood of family size increases also child mortality increases. The results conclude that women’s participation in decision making regarding family size and child mortality is important determinants of family size in Pakistan.